Competitividad turística y desarrollo del turismo comunitario en las comunidades indígenas de la parroquia Calpi, cantón Riobamba, provincia de Chimborazo. - Pilataxi Guailla, Hernan Paul (2023)
The ensuing investigation, "Tourism competitiveness and development of community tourism in the indigenous communities of the Calpi parish, Riobamba canton, Chimborazo Province," aims to determine how tourism competitiveness influences the development of community tourism in the indigenous communities of the Calpi parish, Riobamba Canton, Chimborazo Province, through the independent variable "tourism competitiveness" which is the capacity of a destination to create and integrate value-added products, while its power is measured based on its dimensions as they are: accessibility/connectivity, amplifiers/reducers of the tourist activity and the conditions of the destination/management. The factors present will be subject to research to observe their impact on the dependent variable "community tourism," a management model selfmanaged by the community members themselves and whose value proposition focuses on creating conscious tourism through tourist activities that show daily living. The methodology applied in the subsequent investigation was a documentary, field research, descriptive and qualitative research. The research design is non-experimental, crosssectional, and correlational. The information collected was prepared using investigative instruments such as surveys. The questionnaire was applied to tourists who visited the indigenous communities of La Moya, Jatari Campesino, and Palacio Real. A questionnaire was used for the parish council of Calpi, leaders, and implicit actors in community tourism in the communes above. A specialized statistical software, IBM SPSS Statistics 19, was obtained to process the data collected. As a result, the non-significant relationship of tourism competitiveness with its dimensions: Accessibility/Connectivity, Amplifiers/strongholds of tourist activity, Conditions of the destination/management in the development of community tourism. For the development of the proposal, the situational analysis of all the external forces that condition or will condition the environment of the communities has been proposed; its internal investigation will help accurately determine the most appropriate strategies around the current reality of these communities.